Kepemimpinan Kiai dalam Memelihara Budaya Organisasi di Pondok Modern Gontor , Lirboyo Kediri, dan Pesantren T ebuireng Jombang - Mardiyah Mardiyah (Universitas Darussalam Gontor, 2012)
Islamic Boarding has been known as a model of education institution which has a competitiveness either in the tradition of knowledge seen as one of the great tradition or in its moral transition and transmission internalization. In the other sides, pesantren is also an education that can play the empowerment role and civil society transformation effectively . Kiai as a leader of pesantren has also an important role in developing pesantren tradition to form institution character that can differentiate with the other. Because institution character as organization identity can be meant as a substantial point of the institution competitiveness in forming process that indicates two points, namely: the growth of scientific tradition and the clean system of pesantren education management. This research is to answer research questions by analyzing: 1. the structure of culture organization developed by Kiai as leader, 2. Kiai leadership in keeping culture organization, 3. the similarity and difference of the three pesantren. Based on qualitative paradigm, this research uses qualitative paradigm in terms of phenomenological approarch which is meaningful in comprehending event in relation to people in certain situation. The process of this research uses multi-case studies because it is as inquiry that investigates empirically the phenomena in the real life context. The naturalistic paradigm chooses a sample purposively or by theoretically , three pesantren, namely: Pondok Modern Gontor, Lirboyo Kediri and Pesantren Tebuireng Jombang. The reason of choosing the setting is based on some consideration on their specialty, uniqueness, interest, and suitable with the research topic.